Perspectives in finance and digital transformations in business - Chakrabarti, Satyajit; Chakrabarti, Saikat; Bhandari, Amit Kumar; Saha, Dipak; Mazumdar, Rabin (London Routledge, 2025)
This book presents different perspectives in finance and the adoption of digital tools in business in India. It discusses key issues in strategy, organisation, and management for businesses focussing on practical and actionable guidance and innovative tools which offer insights into the formulation and implementation of effective strategies and solutions.